Skeletal muscle buffering capacity and endurance performance after high-intensity interval training by well-trained cyclists - Weston, A. R.; Myburgh, K. H.; Lindsay, F. H.; Dennis, S. C.; Noakes, T. D.; Hawley, J. A. (European Journal of Applied Physiology, 1997)
Skeletal muscle buffering capacity (beta m), enzyme activities and exercise performance were measured before and after 4 weeks of high-intensity, submaximal interval training (HIT) undertaken by six well-trained competitive cyclists [mean maximal oxygen consumption (VO2max) = 66.2 ml.kg-1.min-1]. HIT replaced a portion of habitual endurance training and consisted of six sessions, each of six to eight repetitions of 5 min duration at 80% of peak sustained power output (PPO) separated by 1 min of recovery. beta m increased from 206.6 (17.9) to 240.4 (34.1) mumol H+.g muscle dw-1.pH-1 after HIT (P = 0.05). PPO, time to fatigue at 150% PPO (TF150) and 40-km cycle time trial performance (TT40) all significantly improved after HIT (P < 0.05). In contrast, there was no change in the activity of either phosphofructokinase or citrate synthase. In addition, beta m correlated significantly with TT40 performance before HIT (r = -0.82, P < 0.05) and the relationship between change in beta m and change in TT40 was close to significance (r = -0.74). beta m did not correlate with TF150. These results indicate that beta m may be an important determinant of relatively short-duration (< 60 min) endurance cycling activity and responds positively to just six sessions of high-intensity, submaximal interval training.